Penerapan Metode Eksperimen Mencampur Warna untuk Mengembangkan Kemampuan Kognitif Anak Kelompok B di RA As-Sholeh Baron - Lilis Rahmawati; Siti Istatik Choiroyaroh (IERA, Islamic Education and Research Academy, 2025)
This study aims to describe the implementation of the color-mixing experiment method in developing the cognitive abilities of Group B children at RA As-Sholeh Baron. This research uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results show that the implementation of the experimental method, using natural materials like dragon fruit and pineapple, was carried out through the stages of preparation, demonstration, direct practice, and discussion. This approach proved effective in developing children's cognitive abilities, particularly in recognizing primary and secondary colors, understanding cause-and-effect relationships, and communicating their findings. Key supporting factors included teacher competence and the availability of facilities, while time management and the need for meticulous preparation were identified as inhibiting factors. This study concludes that the color-mixing experiment method is an effective, contextual, and enjoyable alternative for developing early childhood cognitive abilities, in line with constructivist and cognitive development theories.